Reproduction and food habits analysis of black mullet (Mugil cephalus) in the estuarine waters of Indramayu District, West Java - Herawati, Titin; Ayunikasari, Febri; Rostika, Rita; Iskandar, Iskandar (Acta Aquatica: Aquatic Sciences Journal, 2024)
Indramayu Regency is located in estuarine waters, namely the North Coast of Java Island, the coast which is directly adjacent to the sea with a coastline length of 147 Km makes Indramayu Regency great potential in the field of fisheries. Mullet fish (Mugil cephalus) is a type of fish that has high economic value in the Estuarine Waters of Indramayu Regency. The purpose of the research is to measure reproductive aspects which include sex ratio, gonadal maturity level, gonadal maturity index, fecundity and egg diameter and food habits which include the largest share index and trophic level of black mullet (Mugil cephalus) caught by gill nets used by fishermen. Black mullet (Mugil cephalus) is one of several fish species that have high economic value in the Estuary Waters of Indramayu Regency. This research was conducted in January 2022 - April 2022. Fish samples were taken from the catch of fishermen using a gill net. The results showed that of the 123 mullet fish caught, the ratio of male and female mullet fish was unbalanced, namely 1: 1.8 or 44% for male mullet fish and 56% for female mullet fish. Male mullets are dominant in TKG I and TKG II while female mullets are dominant in TKG III and TKG IV. The fecundity of mullets is quite large at 11,882 - 265,108 grains, Mullet diameter ranges from 0.04 - 0.78 mm with a two-peak distribution mode indicating partial spawning. The preponderance index of mullets shows detritus and phytoplankton as the main feed, zooplankton as complementary feed, and additional feed in the form of animal parts and plant parts. The habit of eating mullets is known as omnivores because mullets eat detritus and phytoplankton as their main food.Keywords: Estuary; Food habits; Indramayu; Mugil chepalus; Reproduction